2023
DOI: 10.1088/1361-6528/acd5da
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the thermal conductivity and diffusivity of graphene nanoplatelets strips: a low-cost technique

Abstract: This paper proposes a new technique to characterize the thermal conductivity and diffusivity of thin strips made by graphene nanoplatelets. The evaluation of these parameters is essential for a reliable design of thermal and electrothermal applications of graphene and is usually performed by means of assessed but expensive techniques such as those based on Raman effects and laser flash. The technique proposed here is simpler and less demanding in terms of equipment, and combines the results of an experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Table 1 summarizes the characteristics of the industrial graphene strips analyzed in this paper (Figure 1b). The electro-thermal properties of these GNP strips are analyzed in [29,31]. The electrical resistivity exhibited by these strips is suitable for their use as heater elements based on the Joule effect, as shown in [29].…”
Section: Gnp Strips Fabrication and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 summarizes the characteristics of the industrial graphene strips analyzed in this paper (Figure 1b). The electro-thermal properties of these GNP strips are analyzed in [29,31]. The electrical resistivity exhibited by these strips is suitable for their use as heater elements based on the Joule effect, as shown in [29].…”
Section: Gnp Strips Fabrication and Characterizationmentioning
confidence: 99%
“…The fitting parameters for the GNP strips and for copper are given in Table 2: compared to copper, the GNP strips exhibit a higher conductivity (more than one order of magnitude), but a negative TCR. The thermal properties of the GNP material analyzed in this paper are instead investigated in [31]; Table 3 summarizes the estimated emissivity (ε) and thermal conductivity (k). As expected, the thermal conductivity value of this industrial graphene is lower than the values expected for pure graphene (that can rise by up to thousands of W/mK, e.g., [48]), but is still of interest, being comparable to those exhibited by conducting materials usually adopted for industrial thermal and electro-thermal applications (like copper, as reported in Table 3).…”
Section: Gnp Strips Fabrication and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation